UV-B Radiation Stress Causes Alterations in Whole Cell Protein Profile and Expression of Certain Genes in the Rice Phyllospheric Bacterium Enterobacter cloacae - Kumar, Jay; Babele, Piyoosh K.; Singh, Divya; Kumar, Ashok (Frontiers in Microbiology, 2016)
Among the different types of UV radiation, UV-B radiation (280-315 nm) has gained much attention mainly due to its increasing incidence on the Earth’s surface leading to imbalances in natural ecosystems. This study deals with the effects of UV-B radiation on the proteome and gene expression in a rice phyllospheric bacterium, Enterobacter cloacae. Of the five bacteria isolated from rice leaves, E. cloacae showed the highest level of resistance to UV-B and total killing occurred after 8 h of continuous exposure to UV-B. Reactive oxygen species (ROS) were induced by UV-B exposure and increased with increasing duration of exposure. Protein profiling by SDS-PAGE and 2-dimensional gel electrophoresis (2-DE) revealed major changes in the number as well as expression of proteins. Analysis of 2-DE gel spots indicated up/down-regulation of several proteins under the stress of UV-B radiation. Thirteen differentially expressed proteins including 2 hypothetical proteins were identified by MALDI-TOF MS and assigned to eight functional categories. Both the hypothetical proteins (gi 779821175 and gi 503938301) were over-expressed after UV-B irradiation; gi 503938301 was characterized as a member of FMN reductase superfamily whereas gi 779821175 seems to be a structural protein as it did not show any functional domain. That the expression of certain proteins under UV-B stress is indeed up-regulated was confirmed by qRT-PCR. Transcript analysis of selected gene including genes of hypothetical proteins (cp011650 and cp002886) showed over-expression under UV-B stress as compared to untreated control cultures. Although this study deals with a limited number of proteins, identification of differentially expressed proteins reported herein may prove useful in future studies especially for assessing their significance in the protection mechanism of bacteria against UV-B radiation stress.